PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS GAME EDUKASI UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR PADA MATA PELAJARAN PANCASILA KELAS IV DI SD INPRES 5/81 WATU KABUPATEN BONE - Hasnimar; Muhajir; Jamaluddin Arifin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The current development of digital technology has a significant impact on education, facilitating the learning process and creating an atmosphere that is not monotonous. This research uses research and development (R&D) methods with the aim of: 1) Understanding the development of educational game learning media, 2) Designing educational game learning media, 3) Assessing the validity of educational game learning media, 4) Assessing the practicality of educational game learning media, 5 ) Assessing the effectiveness of educational game learning media. The research was conducted at SD Inpres 5/81 Watu, Kab. Bone, with 12 students as subjects and 2 validators (material/content and media). Data collection uses a needs identification questionnaire, material/content validation, media validation, field trials, as well as teacher and student responses. The research results show: 1) Student needs are in the required qualifications, 2) Educational game learning media products are designed based on the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model, 3) Validation by material/content and media experts shows very valid qualifications, 4) The practicality of the media as seen from the results of field trials is in very good qualifications, 5) The learning outcomes test (pre-test) is quite effective, and the post-test is very effective. The products developed are valid, practical and effective in improving Pancasila learning.